Useable information for climate resilient design - Marissa K Webber; David R Rounce; Tania Lopez-Cantu; Arthur DeGaetano; Constantine Samaras (Environmental Research Letters)
Climate resilient stormwater infrastructure must be designed to manage precipitation depth and intensity that is projected to increase under climate change. In many countries, including the United States, the current precipitation information used for designing stormwater infrastructure does not include estimates or guidance for designing under climate change. In the contiguous United States, updated precipitation estimates that may be available in 2027 would include adjustment factors to account for climate change, but precipitation estimates also need to explicitly include guidelines for responsible use of precipitation information. We provide practical recommendations for using current precipitation estimates to plan and design climate resilient stormwater infrastructure in the United States until updated precipitation estimates are available. We also recommend guidelines to accompany updated estimates to facilitate the responsible use of precipitation information.